Research on the evaluation indicators of skilled employees' career success based on grounded theory - Fulei Chu; Long Ye; Ming Guo (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: Summarized and sorted career success evaluation indicators of skilled employees. Design/methodology/approach: Based on Grounded Theory, through interviews and questionnaires to railway skilled employees. Findings: the study shows that "subjective career success", including work-family balance, life satisfaction, career satisfaction, perception of career success, "objective career success", including level of total revenue venue, growth rate of wage and times of promotion, "knowledge and skills career success" including upgrade of knowledge and skills, classification of skills, external competitiveness and job autonomy, are three important career success evaluation indicators of skilled employees. Originality/value: The results show that different age groups, different titles and different positions of skilled employees, there is a significant difference in the choice of career success evaluation indicators. It provides a useful reference to establish a career development system for the skilled employees.
Keywords: 650; skilled employees; career success; evaluation indicators; railway industry